2023
DOI: 10.1021/acs.inorgchem.3c00165
|View full text |Cite
|
Sign up to set email alerts
|

[(thf)5Ln(Ge9{Si(SiMe3)3}2)] (Ln = Eu, Sm, Yb): Capping Metalloid Germanium Cluster with Lanthanides

Abstract: We report the synthesis of three neutral complexes with different coordination modes of a di-silylated metalloid germanium cluster to divalent lanthanides [(thf) 5 Ln(η n -Ge 9 (Hyp) 2 )] (Ln = Yb (1, n = 1); Eu (2, n = 2, 3), Sm (3, n = 2, 3); Hyp = Si(SiMe 3 ) 3 ) by the salt metathesis of LnI 2 with K 2 [Ge 9 (Hyp) 2 ] in THF. The complexes were characterized by elemental analysis, nuclear magnetic resonance and UV−vis−NIR spectroscopy, and single-crystal X-ray diffraction. In thf solution, the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
2
3
0
Order By: Relevance
“…Thus, the Stokes shift can be estimated to be 80 nm. This value and that of the FWHM are typical for molecular Eu 2+ complexes 17 and especially close to the emission and excitation spectra of the recently reported europium complex with disubstituted germanium cluster ligand [(thf) 5 Eu(Ge 9 (Hyp) 2 )] 9 and EuI 2 in thf. 16,18…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Thus, the Stokes shift can be estimated to be 80 nm. This value and that of the FWHM are typical for molecular Eu 2+ complexes 17 and especially close to the emission and excitation spectra of the recently reported europium complex with disubstituted germanium cluster ligand [(thf) 5 Eu(Ge 9 (Hyp) 2 )] 9 and EuI 2 in thf. 16,18…”
supporting
confidence: 87%
“…Thus, the Stokes shift can be estimated to be 80 nm. This value and that of the FWHM are typical for molecular Eu 2+ complexes 17 and especially close to the emission and excitation spectra of the recently reported europium complex with disubstituted germanium cluster ligand [(thf) 5 Eu(Ge 9 (Hyp) 2 )] 9 and EuI 2 in thf. 16,18 In order to asses these spectra we have measured the luminescence of EuI 2 and bis-ligand compound [(thf) 2 Eu (Ge 9 (Hyp) 3 ) 2 ] 5 under the same conditions (see ESI †).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The latter ones have recently shown a new facet of metalloid germanium clusters, namely, activity in homogeneous catalysis. In addition to η-coordination, some metal compounds lead to cluster expansion and the formation of closo clusters . Very recently, in our research group, a successful formation of complexes with f elements has been demonstrated …”
Section: Introductionmentioning
confidence: 97%